Pengaruh Kualitas Produk, Harga, dan Iklan Televisi Terhadap Keputusan Pembelian Kosmetik Merek Citra Hand And Body Lotion di Pariaman - Erdalina, Wahyu (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT - SEKOLAH TINGGI ILMU EKONOMI SAKTI ALAM KERINCI, 2018)
The development of cosmetic products has resulted in increasingly tight competition in the cosmetics business world, so that each cosmetic manufacturer is competing to win the competition. Each company tries to create a marketing concept that is able to attract consumers to buy products offered. In addition, the company also develops its knowledge about consumer behavior. This is because consumer behavior is very influential on consumer interest to make repurchase decisions on products offered. Consumer decisions in determining or choosing a particular product brand are not things that just happen. Many considerations are taken by consumers before deciding to buy a product, such as product quality, price, and promotion of the product. This research was conducted in 2O14 in Kota Pariaman. The population of this study were women aged 15-35 years who had used brand beauty products, hand and body lation images around Pariaman. Based on the results of the calculation, the minimum number of samples is 96 respondents. But in this study will take a sample exceeding the minimum number of 100 respondents. The number of respondents as many as 100 people is considered to be representative because it is greater than the minimum sample size. The results showed that the quality of products, prices and television advertisements had a significant effect on the purchase decision of brand image cosmetics and hand and body lotion in Pariaman